Development of LAG-3/FGL1 blocking peptide and combination with radiotherapy for cancer immunotherapy - Yuzhen Qian; Yixuan Sun; Peishang Shi; Xiuman Zhou; Qiongqiong Zhang; Qingyu Dong; Shengzhe Jin; Lu Qiu; Xiaoshuang Niu; Xiaowen Zhou; Wenshan Zhao; Yahong Wu; et al. (Elsevier, 2024)
Aside from antibodies, peptides show great potential as immune checkpoint inhibitors (ICIs) due to several advantages, such as better tumor penetration and lower cost. Lymphocyte-activation gene 3 (LAG-3) is an immune checkpoint which can induce T cell dysfunction through interaction with its soluble ligand fibrinogen like protein-1 (FGL1). Here, we found that LAG-3 expression was higher than programmed cell death protein 1 (PD-1) in multiple human cancers by TCGA databases, and successfully identified a LAG-3 binding peptide LFP-6 by phage display bio-panning, which specifically blocks the interaction of LAG-3/FGL1 but not LAG-3/MHC-II. Subsequently, d-amino acids were introduced to substitute the N- and C-terminus of LFP-6 to obtain the proteolysis-resistant peptide LFP-D1, which restores T cell function in vitro and inhibits tumor growth in vivo. Further, a bispecific peptide LFOP targeting both PD-1/PD-L1 and LAG-3/FGL1 was designed by conjugating LFP-D1 with PD-1/PD-L1 blocking peptide OPBP-1(8-12), which activates T cell with enhanced proliferation and IFN-γ production. More importantly, LFOP combined with radiotherapy significantly improve the T cell infiltration in tumor and elevate systemic antitumor immune response. In conclusion, we developed a novel peptide blocking LAG-3/FGL1 which can restore T cell function, and the bispecific peptide synergizes with radiotherapy to further enhance the antitumor immune response.